A Delphi Based Approach to the Assessment of New Marine Litter Reduction and Processing Technologies - Cunha, Maria C.; Marques, João; Dias, Luis C.; Cotera, Ignacio Rada; Triantaphyllidis, George (Frontiers in Marine Science, 2022)
This work presents the most important aspects that should be considered for assessing new marine litter reduction and processing technologies. The most relevant technology features are highlighted using a Delphi method capable of gathering and handling a large quantity of valuable data in areas where information is lacking. This relies on judgements provided by recognized experts in a particular area of knowledge, through an organized procedure based on a structured questionnaire and its reiterations. The Delphi process developed in this study completed two rounds. In the first round, a questionnaire with 55 statements (potentially important aspects) was shared with experts and stakeholders from different types of institutions (Administrations, Marinas and Ports; Associations; Companies; Universities; and Research Centers). Appropriate statistical analysis of the responses determined the degree of consensus and the level of importance perceived for each aspect. Feedback information based on analysis of the answers provided during the first round was included in a second round of the survey that focused on the statements that did not gather enough consensus, and therefore needed to be reevaluated by the expert group. After checking the stability of the results between rounds, the conclusions are set out and a list of the aspects to be considered in different decision-making contexts is drawn (from technology development, investment to marketing and policy making) taking into account technical, environmental, socio-economic, and political issues.